Gastric cancer: surgery in 2011 - Ott, Katja; Lordick, Florian; Blank, Susanne; Büchler, Markus W. (Langenbeck's archives of surgery, 2011)
Treatment of gastric cancer is more and more becoming an individualized decision. The choice of the optimal approach is based on prognostic factors, on the anatomic site of the tumor, and on expectations about the response to neoadjuvant treatment. Early gastric cancer that is limited to the mucosal layer is the domain of endoscopic resections. As soon as the submucosal layer is invaded, surgical strategies with adequate lymphadenectomy become necessary.
Gesehen am 19.10.2022